CTNI-12. PHASE II MULTICENTRIC ITALIAN TRIAL ON REPOSITIONING OF THE ANTIPSYCHOTIC DRUG CHLORPROMAZINE AND ITS SYNERGISM WITH TEMOZOLOMIDE IN MGMT UNMETHYLATED GLIOBLASTOMA PATIENTS: THE RACTAC TRIAL. (12th November 2021) - Pace, Andrea; Lombardi, Giuseppe; Matteoni, Silvia; Villani, Veronica; Abruzzese, Caludia; Cerretti, Giulia; Padovan, Marta; Caccese, Mario; Benincasa, Dario; Silvani, Antonio; Paggi, Marco
Abstract: The poor prognosis of patients affected by glioblastoma (GBM) prompts the search for new and more effective therapies, particularly for GBMs with unmethylated MGMT. In this regard, drug repurposing, can represent a safe and inexpensive way to bring novel pharmacological approaches from bench to bedside. Chlorpromazine, a medication in use since six decades for the therapy of psychiatric disorders, shows in vitro features that make it eligible for repositioning in GBM therapy. In our experimentation on six GBM cell lines, chlorpromazine inhibited cell viability in an apoptosis-independent way, induced polyploidy, reduced cloning efficiency as well as neurosphere formation and downregulated the expression of stemness genes. Notably, we found that chlorpromazine synergized with temozolomide, in reducing cell viability and strongly cooperated in reducing cloning efficiency and inducing cell death in vitro for all the GBM cell lines assayed. With these assumptions, we started a multicentric Phase II clinical trial on newly diagnosed GBM patients with unmethylated MGMT by adding chlorpromazine to temozolomide in the adjuvant phase of the standard first-line therapeutic protocol. The experimental procedure involves the combination of CPZ with standard treatment with TMZ in the adjuvant phase of the Stupp protocol. CPZ is administered orally at a dose of 50 mg/day – GG 1-28 – of every cycle of the adjuvant treatment with TMZ. At present, 28 patients out of 41 patients planned have been enrolled, without relevant toxicity.